LITERATURE STUDY OF THE DYNAMICS OF INDONESIAN HALAL CERTIFICATION - Nirmadarningsih Hiya; Zuhrinal M. Nawawi (CERED Indonesia Institute, 2021)
This study examines research related to “Halal Certification” in national journal articles. Using descriptive statistical analysis and narrative review of 18 publication articles related to